(untitled) (Bangladesh Pharmaceutical Journal, 2020)
Aeschynomene aspera (Family- Fabaceae), a traditionally used medicinal plant, is aquatic, perennial, erect subshrub up to 200 cm tall with compound leaves and locally it is called Shola (Bangladesh), Laugaun (India). The study started with phytochemical screening of ethanolic leaf extract of A. aspera followed by bioactivity study such as in-vitro antioxidant activity by free radical (DPPH) scavenging assay, estimation of total phenolic as well as total flavonoid contents and the analgesic, antidiarrheal and anthelmintic activities. Analgesic, antidiarrheal and anthelmintic activities were evaluated by acetic acid induced writhing inhibition in mice, castor oil induced diarrheal episode in mice and using living parasites Haemonchus contortus, respectively. The presence of carbohydrate, reducing sugar, glycosides, tannins, alkaloids, steroids, gums and flavonoids was estimated with the help of phytochemical screening. In DPPH scavenging assay the extract showed IC50 value of 86.14μg/mL where ascorbic acid showed 12.02μg/mL. It also exhibited total phenolic and flavonoid contents as 461.09 GAE/100g and 297.20mg Quercetin/100g of dried plant extract. About 36% and 61% writhing inhibitions were observed in mice at 250 and 500mg/kg doses of A. aspera leaf extract, respectively. Anthelmintic activity showed by the extract was dose dependent. The extract also showed 46.01 and 71.68% inhibition of defecation in mice at doses 250 and 500 mg/kg, respectively. All these suggest that the A. aspera extract possesses antioxidant, analgesic, anthelmintic and antidiarrheal activities. Bangladesh Pharmaceutical Journal 23(2): 109-116, 2020